Trend in alcohol use in Australia over 13 years: has there been a trend reversal?. (December 2016) - Chan, Gary; Leung, Janni; Quinn, Catherine; Connor, Jason; Hides, Leanne; Gullo, Matthew; Alati, Rosa; Weier, Megan; Kelly, Adrian; Hall, Wayne
Abstract Background Skog's collectivity theory of alcohol consumption predicted that changes in alcohol consumption would synchronize across all types of drinkers in a population. The aim of this paper is examine this theory in the Australian context. We examined whether there was a collective change in alcohol use in Australia from 2001 to 2013, estimated alcohol consumption in non-high risk and high risk drinkers, and examined the trends in alcohol treatment episodes. Methods Data from the 2001–2013 National Drug Strategy Household Surveys (N = 127, 916) was used to estimate the prevalence and alcohol consumption of abstainers, high risk drinkers and frequent heavy episodic drinkers. Closed treatment episodes recorded in the Alcohol and Other Drug Treatment Services National Minimum Dataset (N = 608, 367) from 2001 to 2013 were used to examine the trends of closed alcohol treatment episodes. Results The prevalence of non-drinkers (abstainers) decreased to the lowest level in 2004 (15.3 %) and rebounded steadily thereafter (20.4 % in 2013;p < .001). Correspondingly, the per capita consumption of high risk drinkers (2 standard drinks or more on average per day) increased from 20.7 L in 2001 to peak in 2010 (21.5 L;p = .020). Non-high risk drinkers' consumption peaked in 2004 (2.9 L) and decreased to 2.8 L in 2013 (p < .05). There were decreases in alcohol treatment episodes across nearly all birth cohorts in recent years. Conclusion These findings are partially consistent with and support Skog's collectivity theory. There has been a turnaround in alcohol consumption after a decade-long uptrend, as evident in the collective decreases in alcohol consumption among nearly all types of drinkers. There was also a turnaround in rate of treatment seeking, which peaked at 2007 and then decreased steadily. The timing of this turnaround differs with level of drinking, with non-high risk drinkers reaching its peak consumption in 2004 and high risk drinkers reaching its peak consumption in 2010.